A Randomized Phase 1/2 Study of a Respiratory Syncytial Virus Prefusion F Vaccine. (21st December 2021) - Walsh, Edward E; Falsey, Ann R; Scott, Daniel A; Gurtman, Alejandra; Zareba, Agnieszka M; Jansen, Kathrin U; Gruber, William C; Dormitzer, Philip R; Swanson, Kena A; Radley, David; Gomme, Emily; Cooper, David; et al.
Abstract: Background: Protection against human respiratory syncytial virus (RSV) remains an unmet need potentially addressable by maternal immunization. This phase 1/2 study evaluated a bivalent prefusion F vaccine (RSVpreF) with antigens from RSV subgroups A and B. Methods: Adults 18–49 years old (N = 618) were randomized to receive placebo or 60, 120, or 240 µg RSVpreF with or without Al(OH)3 . Safety and immunogenicity were evaluated. Results: RSVpreF recipients more frequently reported local reactions and systemic events than placebo recipients; these were mostly mild or moderate. No vaccine-related serious adverse events occurred through 12 months postvaccination. All RSVpreF formulations induced 1-month postvaccination virus-neutralizing titers higher than those associated with protection of high-risk infants by palivizumab, the only prophylactic currently available for RSV. Geometric mean fold rises (GMFRs) across RSVpreF doses/formulations were 10.6–16.9 for RSV A and 10.3–19.8 for RSV B at 1 month postvaccination, greater than those historically elicited by postfusion F vaccines. GMFRs were 3.9–5.2 and 3.7–5.1, respectively, at 12 months postvaccination. Conclusions: RSVpreF formulations were safe, well tolerated, and induced robust neutralizing responses in adults. These findings support development of RSVpreF, which is being evaluated in a pivotal phase 3 study for maternal immunization. Clinical Trials Registration: NCT03529773. Abstract : Respiratory syncytial virus stabilized prefusion F subunit vaccine (RSVpreF) formulations were well tolerated and highly immunogenic in younger adults. These findings support further development of RSVpreF in a pivotal phase 3 study for maternal immunization.